Gross and Histopathological Study of Postscabietic Nodules - Nada Hamzah Shareef Al Shabbani; Marwa Jamal Hussain Al Kinani; Tmara Qais Al-mohammadi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Background: Nodular postscabietic scabies refer to the persistent intermittent signs of scabies that are seen in active and post-treatment period that might last for months. The spectrum of clinico-morphological ranges that can be observed with sarcoptic nodules is broad, and most of the entity's criteria can be elicited histopathologically and pathologically. The management of such nodules may be a challenge. They are commonly treated through local application of corticosteroids or injection of corticosteroids to nodules but the response to treatment is less than clent and relapses are very frequent. The objective of this study was to illuminate which of these features prevail and which ones fade in scarred sites which undergo postscabietic nodule development. The time span between August 2021 to May 2022 was allowed to collect samples from patients with (1-60) years old and full of scabies burrows who visit teaching hospitals and private dermatology clinics in Kut, Wasit Province, Iraq. Treat groups were split into 30 females, and 20 males; with persistent itchy nodular lesions of scabies demonstrated clinically and histopathologically. Everity grade scabies was evaluated by the number of lesions and rated it as severity of itching. Long-term treatment with topical glucocorticoids for 14 days in every age. Tissue from the blisters of patient was obtained after medication. The specimens were washed, fixed and cut to 4-5 µm and stained with H&E. The staining allowed us to observe the fragments of tissues under light microscope with different magnification power. We have observed excessive males and the prevalence of SCABies were more in a young adult group in comparison with other age groups. It was found that lesions with wiry projections tended to persist for two weeks to 52 weeks and the number of nodules had varied from one to fourteen lesions. Examination of Histopathological slide showing acanthosis in 80, histolymphocytic infiltration in 76, and eosinophilia in 100 of total cases in the whole period. After the scabitic nodule loop, the body experiences a hypersensitivity reaction. From the three hundred cases examined microscopically, most (80%) of them were found to be characterized by acanthotic epidermis and diffuse dense dermal lymphocytic infiltration. Neutrophilic reaction, epithelioid-granulomatous inflammation and eosinophilia have been diagnosed in 76 % sight upon while 100 % of other nodules have shown eosinophilia.